Anti-atomic oxygen / antistatic / ultraviolet-resistant composite protective coating as well as preparation method and application thereof
Through the composite protective coating composed of sulfur-doped ternary hydrotalc nanosheet composite material and silane coupling agent, the problem of spacecraft surface materials being easily damaged in low-Earth orbit environments is solved, and multifunctional protection against atomic oxygen, anti-static and ultraviolet resistance is achieved, which enhances the adhesion and flexibility of the coating, and meets the needs of long-term service.
Patent Information
- Application Number
- CN202311105618.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2025-02-28
AI Technical Summary
Existing spacecraft surface polymer materials are susceptible to damage from atomic oxygen, static electricity and ultraviolet radiation in low-Earth orbit environments, resulting in material failure and damage. The existing protective coatings are prone to cracking and peeling, making it difficult to meet the needs of long-term service.
The anti-atomic oxygen/antistatic/ultraviolet-resistant composite protective coating composed of sulfur-doped ternary hydrotalcite nanosheet composite material and silane coupling agent is used to regulate the microstructure and composition of the material, and the protective performance of the coating is improved, and the binding force between the coating and the substrate is enhanced through heat treatment.
It realizes effective anti-atomic oxygen, anti-static and ultraviolet-resistant multifunctional protection in low-earth orbit environments, enhances the flexibility and adhesion of the coating, avoids cracking and peeling, and meets the long-term service needs of spacecraft surface materials.
Smart Images

Figure CN119529358A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a space anti-proton oxygen / anti-static / ultraviolet-resistant composite protective coating and a preparation method and application thereof, and specifically to a sulfur-doped hydrotalcite-like anti-proton oxygen / anti-static / ultraviolet-resistant composite protective coating and a preparation method thereof. The coating is mainly used to meet the multifunctional protection requirements of anti-proton oxygen, anti-static and ultraviolet-resistant for low-orbit spacecraft, and belongs to the technical field of aerospace material space environment protection application. Background Art
[0002] In order to achieve the goal of lightweight and easy processing of aerospace materials, polymer materials have been widely used on the surface of current spacecraft due to their advantages such as good high and low temperature resistance, good optical properties, and excellent mechanical properties. Spacecraft operate in low Earth orbit (LEO) 200-700km from the earth. There are environmental factors such as atomic oxygen (AO), plasma, and ultraviolet radiation in the environment, which will have a significant destructive effect on polymer materials exposed on the surface, resulting in material damage and failure. Under the action of atomic oxygen, polymer materials will undergo oxidative destruction of the molecular structure, resulting in quality loss; and because polymer materials have high insulation, when plasma gathers on the surface of the material, a short-term discharge will occur to further break down the material. In addition, ultraviolet rays will cause significant structural changes in polymer materials under the action of vacuum, and the transmittance and thermal properties will change. Therefore, effective protection of polymer materials to achieve the functional characteristics of anti-oxygen, anti-static, and ultraviolet resistance has become a key way to achieve the long-term in-orbit service of polymer materials.
[0003] The protection methods of polymer surface anti-proton oxygen / antistatic / UV resistance can be mainly divided into bulk modification and surface modification. These two methods can achieve the protection requirements to different degrees. Generally speaking, bulk modification is to introduce elements with certain functional characteristics into the polyimide substrate by chemical methods to achieve the protection goal of polymer materials. However, bulk modification is easy to have an adverse effect on the polymer structure. When the content of protective elements is low, it is difficult to form a continuous and dense protective structure. As the protective performance of the polymer is improved, its mechanical properties will decrease. Surface modification is to prepare a layer of protective coating on the polymer surface by physical and chemical methods, which has no significant effect on the relevant properties of the substrate. Among them, inorganic coatings have become the focus of current research due to their excellent protective properties. However, dense inorganic coatings are usually brittle and prone to cracking during use. Moreover, due to the large difference in mechanical properties between the inorganic coating and the substrate, it is easy to separate and fall off from the substrate surface, which has become one of the bottleneck problems in current applications.
[0004] Therefore, the preparation of flexible, anti-oxidant, anti-static, and UV-resistant coatings that are resistant to peeling and cracking is of great significance for achieving long-term service of polymer materials on the surface of spacecraft. Summary of the invention
[0005] In response to the above problems, the present invention proposes a composite protective coating with anti-oxygen / anti-static / ultraviolet resistance functions and a preparation method thereof. By regulating the composition and microstructure of the coating, the anti-oxygen, anti-static and ultraviolet resistance of the coating are improved, aiming to meet the use requirements of spacecraft materials in space environments.
[0006] In the first aspect, the present invention provides an anti-proton oxygen / antistatic / ultraviolet resistant composite protective coating, comprising: a polymer matrix, and a sulfur-doped ternary hydrotalcite protective layer formed on the surface of the polymer matrix; the sulfur-doped hydrotalcite protective layer comprises a silane coupling agent and a sulfur-doped ternary hydrotalcite nanosheet composite material.
[0007] In the present invention, a coating having anti-proton oxygen / antistatic / ultraviolet resistant functions of a sulfur-doped ternary hydrotalcite composite system is provided. In the present invention, the anti-proton oxygen / antistatic / ultraviolet resistant composite protective coating comprises: a flexible multi-element coating formed by a nano-sheet hydrotalcite having a regular hexagonal structure and a small amount of a silane coupling agent. The present invention synthesizes a hydrotalcite having a ternary metal component by introducing a transition metal, and further achieves a narrowing of the microstructure band gap in two steps through vulcanization, and the narrowing of the band gap can effectively achieve the improvement of conductivity and anti-ultraviolet performance. At the same time, the present invention increases the bonding between the organic matrix and the inorganic coating by utilizing the amino and hydroxyl groups after hydrolysis of the silane coupling agent to bond with the hydroxyl groups on the surface of the hydrotalcite nanosheets and the hydroxyl and carboxyl groups on the surface of the polyimide. The sulfur-doped ternary hydrotalcite composite system with a layered structure can narrow the band gap by introducing heteroatoms, and the unique non-dense layered structure can realize the adsorption and rebound of atomic oxygen. The formed three-dimensional conductive network will effectively prevent electrostatic breakdown caused by local discharge, and utilize the matching band gap to absorb ultraviolet light to achieve ultraviolet protection for polyimide.
[0008] Preferably, the molar chemical composition of the sulfur-doped ternary hydrotalcite nanosheet composite material is [M 2+ (1-x) / 3 M 2 + (2-2x) / 3 M 3+ x S y 2- (OH) 2-2y ] x+ A n- x / n mH2O, where M 2+is a divalent metal cation, preferably Mg 2+ 、Ni 2+ 、Co 2+ 、Zn 2+ , Cu 2+ At least two of M 3+ is a trivalent metal cation, preferably Al 3+ Cr 3+ , Fe 3+ Sc 3+ At least one of n- For CO3 2- 、NO3 - , Cl - OH - 、SO4 2- PO4 3- 、C6H4(COO)2 2- At least one of; x=0.17~0.33.
[0009] Preferably, the sulfur-doped ternary hydrotalcite-like composite material has 2+ 、M 2+ 、M 3+ The molar ratio is (0.67-1.65):(1.36-3.24):1, preferably 1:2:1.
[0010] Preferably, the thickness of the hydrotalcite-like nanosheets in the sulfur-doped ternary hydrotalcite-like nanosheet composite material is 0.5 to 20 nm, and the diameter of the circumscribed circle is 50 to 500 nm; Among them, sulfur-doped ternary hydrotalcite nanosheet composites self-assemble to form a three-dimensional conductive network.
[0011] Preferably, the silane coupling agent is selected from at least one of aminohydrocarbon silane, 3-mercaptopropyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane and 3-methacryloxypropyltrimethoxysilane; the aminohydrocarbon silane is selected from at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and N-aminoethyl-3-aminopropyltriethoxysilane, preferably 3-aminopropyltriethoxysilane; The silane coupling agent simultaneously undergoes bonding reactions with the polymer matrix and the sulfur-doped ternary hydrotalcite nanosheet coating.
[0012] In the present invention, doping is used to achieve the regulation of the material band structure, shorten the band gap of the material, and realize the functions of anti-proton oxygen / antistatic / ultraviolet resistance from the microstructure level. The bonding effect of the silane coupling agent, the polymer matrix, and the sulfur-doped ternary hydrotalcite coating is used to achieve good adhesion between the coating and the substrate.
[0013] Preferably, the ratio of the sulfur-doped ternary hydrotalcite nanosheet composite material to the silane coupling agent is 10 mg: (0.1-10) μL.
[0014] Preferably, the thickness of the sulfur-doped ternary hydrotalcite protective layer is 50 nm to 10 μm.
[0015] Preferably, the polymer matrix is a polymer matrix containing hydroxyl groups and carboxyl groups or a polymer matrix whose surface is modified to generate hydroxyl groups and carboxyl groups, preferably a polyimide matrix, a fluoroplastic matrix (such as polytetrafluoroethylene, etc.) or a polyester matrix.
[0016] In a second aspect, the present invention provides a method for preparing an anti-oxygen / antistatic / ultraviolet resistant composite protective coating, comprising: A silane coupling agent is added to an aqueous dispersion containing a sulfur-doped ternary hydrotalcite nanosheet composite material and mixed, and then coated on the surface of a polymer substrate, and finally heat-treated at 80-200° C. for 3-12 hours to obtain the anti-proton oxygen / antistatic / ultraviolet resistant composite protective coating.
[0017] Preferably, the total concentration of the sulfur-doped ternary hydrotalcite nanosheet composite material in the aqueous dispersion containing the sulfur-doped ternary hydrotalcite nanosheet composite material is 1 to 50 mg / mL, preferably 20 mg / mL;
[0018] Preferably, the polymer matrix is surface modified to form groups containing hydroxyl groups and carboxyl groups; Preferably, the surface of the polymer matrix is subjected to alkali-acid modification; the alkali-acid modification includes alkali treatment and acid treatment. More preferably, the polymer matrix is treated in a 0.1-6 mol / L NaOH solution and a 0.1-6 mol / L acetic acid solution for 0.2-6 h, respectively, and then washed and dried to obtain a polymer matrix having surface active groups (hydroxyl, carboxyl).
[0019] Preferably, the coating is applied at least once; The coating includes spin coating, drop coating, spray coating or blade coating; Preferably, the spin coating speed is 300 to 2000 rpm, and the spin coating time is 6 to 18 seconds; Preferably, after each coating, preliminary drying is performed, the preliminary drying temperature is 40 to 100° C., and the preliminary drying time is 5 to 50 seconds.
[0020] Furthermore, preferably, the method for preparing the aqueous dispersion containing the sulfur-doped ternary hydrotalcite nanosheet composite material comprises: (1) calcining a ternary hydrotalcite powder at 250 to 550° C. for 2 to 6 hours to obtain a ternary oxide powder; (2) uniformly blending the obtained ternary oxide powder and a sulfur source, and sulfurizing them in an inert atmosphere at 150 to 400° C. for 1 to 5 hours to obtain a sulfide / ternary oxide mixture; the mixing method is grinding. (3) dissolving the sulfide / ternary oxide mixture in deionized water at 40 to 100° C. and stirring for 2 to 10 hours to obtain the sulfur-doped ternary hydrotalcite nanosheet composite material; Preferably, the sulfur source is at least one of thiourea, elemental sulfur, thioacetamide, mercaptan, and sodium sulfide.
[0021] Furthermore, preferably, the method for preparing the ternary hydrotalcite nanosheet powder comprises: (1) M 2+ Salt, M 3+ Salt is added as a hydrotalcite precursor to deionized water, and then an alkali solution is added and stirred to adjust the pH to 9-10, and the mixture is stirred evenly and then allowed to stand to obtain a suspension; (2) washing the obtained suspension to obtain a precipitate dispersion; (4) hydrothermally treating the obtained precipitate dispersion at 80 to 200° C. for 6 to 48 hours to obtain an aqueous dispersion containing ternary hydrotalcite nanosheets; (5) centrifugally drying the obtained uniform dispersion to obtain ternary hydrotalcite nanosheet powder; Preferably, the alkaline solution is aqueous ammonia; Preferably, the concentration of the precipitate dispersion is 1 to 50 mg / mL.
[0022] In a third aspect, the present invention provides an application of an anti-oxygen / anti-static / ultraviolet-resistant composite protective coating in the field of space environment.
[0023] Beneficial effects of the present invention: The present invention provides a composite material system of a sulfur-doped ternary hydrotalcite coating. A ternary hydrotalcite precipitate dispersion is synthesized by a hydrothermal growth method, and further vulcanized to form a three-dimensional sulfur-doped ternary hydrotalcite nanosheet conductive network, which has excellent anti-oxygen, antistatic and UV resistance properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a light microscopic photograph of the surface of the sulfur-doped ternary hydrotalcite-like coating in Example 1. It can be seen from the figure that a uniform coating structure is successfully coated. It can be seen from the figure that a uniform coating structure is successfully coated; Figure 2 This is a cross-sectional SEM image of the sulfur-doped ternary hydrotalcite-like coating in Example 1. It can be seen from the image that the coating thickness is about 1.1 microns; Figure 3This is the distribution of elements in the EDS selected area scan of the sulfur-doped ternary hydrotalcite coating surface in Example 1. It can be seen from the figure that the layer includes magnesium, aluminum, nickel, sulfur, carbon, oxygen, silicon, chlorine and other elements. Among them, magnesium, aluminum, nickel, and sulfur account for 9.66%, 4.47%, 1.63%, and 2.20% respectively; Figure 4 This is the Fourier infrared characterization spectrum of the surface functional groups of the sulfur-doped ternary hydrotalcite-like coating in Example 1. It can be seen from the figure that it contains obvious -OH of hydrotalcite, as well as C-OH, Si-C formed by polyimide modification, Si-O formed by hydrolysis of APTES and other bonding forms. Figure 5 This is a light microscope picture of the sulfur-doped ternary hydrotalcite-like coating in Example 1 after the adhesion is tested by the cross-hatch method. It can be seen from the picture that it has good adhesion; Figure 6 This is a light microscope picture of the sulfur-doped ternary hydrotalcite coating without amino-hydrocarbon silane coupling agent in Example 5 after the adhesion is tested by the cross-hatch method. It can be seen from the picture that the adhesion is poorer than that of the coating with APTES added; Figure 7 These are optical microscope comparison pictures of the sulfur-doped ternary hydrotalcite-like coating in Example 1 before and after the ground atomic oxygen simulation test. From the pictures, it can be seen that the coating has no obvious surface damage after atomic oxygen bombardment and has good stability. DETAILED DESCRIPTION
[0025] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0026] In the present disclosure, the anti-proton oxygen / antistatic / ultraviolet resistant composite protective coating comprises: a flexible multi-element coating formed by sulfur-doped ternary hydrotalcite nanosheets with a regular layered structure and a small amount of silane coupling agent. The coating and the substrate are connected by the silane coupling agent in the coating and have a certain bonding force. The protective coating described in the present invention is composed of a protective main material sulfur-doped ternary hydrotalcite nanosheets and a silane coupling agent that enhances the bonding force. The formed layered structure can effectively rebound or adsorb when facing atomic oxygen invasion. The sulfur-doped ternary hydrotalcite nanosheets with a regular layered structure can enhance conductivity, have excellent resistance to plasma and ultraviolet radiation in the space environment, and have excellent anti-flaking and cracking performance, and can be widely used in the aerospace field.
[0027] In an optional embodiment, the chemical composition of the sulfur-doped hydrotalcite nanosheets or hydrotalcite-like nanosheets of a certain size can be expressed as [M 2+ (1-x) / 3 M 2+ (2-2x) / 3 M 3+x S y 2- (OH) 2-2y ] x+ A n- x / n ·mH2O, in which sulfur element partially replaces OH to form sulfide. 2+ For divalent metal cations, such as Mg 2+ 、Ni 2+ 、Co 2+ 、Zn 2+ , Cu 2+ etc.; M 3+ For trivalent metal cations, such as Al 3+ Cr 3+ , Fe 3+ Sc 3+ etc. n- Anions, such as CO3 2- 、NO3 - , Cl - OH - 、SO4 2- PO4 3- 、C6H4(COO)2 2- Inorganic and organic ions and complex ions; x ranges from 0.1 to 0.5, preferably from 0.2 to 0.33. The preferred composition is divalent metal cations, trivalent metal cations, divalent metal cations, and anions are Mg 2+ 、Al 3 + , Cu 2+ / Ni 2+ / Co 2+ , Cl - , and Mg 2+ :Al 3+ :X 2+ =2:1:1.
[0028] In an optional embodiment, the sulfur-doped ternary hydrotalcite-like nanosheets with regular morphology are prepared by blending, hydrothermal growth, and sulfurization processes, and are a composite structure of stacked nanosheets.
[0029] In an optional embodiment, the thickness of the anti-oxygen / antistatic / ultraviolet resistant composite protective coating may be 200 nm to 10 μm.
[0030] The following is an exemplary description of the preparation process of the layered sulfur-doped ternary hydrotalcite-like nanosheets anti-proton oxygen / antistatic / ultraviolet resistant composite protective coating of the present invention.
[0031] Preparation of a dispersion containing sulfur-doped ternary hydrotalcite nanosheets. Preferably, it is obtained by coprecipitation, hydrothermal method, and sulfurization doping. Taking the preferred sulfur-doped nickel-magnesium-aluminum ternary hydrotalcite as an example, the steps of blending, hydrothermal growth, and sulfurization to prepare hydrotalcite-like layered nanosheets include: dissolving magnesium chloride hexahydrate, aluminum chloride hexahydrate, and nickel chloride hexahydrate in deionized water, stirring to prepare a uniform solution, adding ammonia water and stirring to adjust the pH to 9-10, and standing after stirring. The resulting suspension is washed with deionized water and then placed in a 150°C oven for hydrothermal heating for 24 hours. The obtained hydrotalcite solution is centrifuged and dried, and the precipitate is collected and dried, and the powder is calcined at 250-550°C for 2-6 hours, mixed with thiourea after calcination, and sulfurized at 150-400°C in an argon atmosphere for 1-5 hours. The powder obtained by sulfurization is dissolved in hot water at 40-100°C and stirred for 2-12 hours to obtain a dispersion of sulfur-doped ternary hydrotalcite nanosheets.
[0032] A certain amount of silane coupling agent is added to the dispersion containing sulfur-doped ternary hydrotalcite nanosheets as a crosslinking agent, and then after stirring for a certain period of time at room temperature, it is coated on the polymer substrate to form a wet film. The stirring speed is 200-600 rpm and the time is 10-60 minutes (for example, 20 minutes).
[0033] In an optional embodiment, the coating method is any one of spin coating, drop coating, spray coating, blade coating or dip coating, preferably spin coating, and the number of coatings is preferably 14 times.
[0034] In an optional embodiment, the heat treatment temperature is a gradient temperature increase process formed by several temperature values within the range of 80 to 200° C. The total time of the heat treatment can be 2 to 20 hours. Preferably, the heat treatment process is 80° C., 110° C., and 150° C. for 1 hour, 1 hour, and 3 hours, respectively.
[0035] Specifically, a sulfur-doped nickel-magnesium-aluminum ternary hydrotalcite-like coating with a magnesium-aluminum-nickel atomic ratio of 2:1:1 is taken as an example to illustrate the preparation method of the anti-proton oxygen / antistatic / ultraviolet resistant composite protective coating.
[0036] Preparation of sulfur-doped ternary hydrotalcite nanosheet dispersion. Disperse magnesium chloride hexahydrate, aluminum chloride hexahydrate, and nickel chloride hexahydrate in 200 ml of deionized water, stir evenly at room temperature, add ammonia water and stir to adjust the pH to 9-10, stir evenly and let stand. Wash the obtained suspension several times with deionized water. After washing, prepare a dispersion with a mass concentration of 1-50 mg / mL (e.g., 20 mg / mL). Then, place the dispersion in a 150°C oven for hydrothermal treatment for 24 hours, and finally obtain a ternary hydrotalcite nanosheet dispersion. The obtained uniform dispersion is centrifuged and dried to obtain a ternary hydrotalcite nanosheet powder. The ternary hydrotalcite powder is calcined at 450°C in a tube furnace for 5 hours to obtain a ternary oxide. The obtained ternary oxide powder is uniformly blended with thiourea and sulfurized at 250°C in an argon atmosphere for 2 hours to obtain a sulfide / ternary oxide mixture. The mixture was dissolved in deionized water at 80° C. and stirred for 6 hours to form a uniform and stable solution, thereby obtaining a sulfur-doped ternary hydrotalcite nanosheet dispersion.
[0037] Preparation of sulfur-doped ternary hydrotalcite nanosheets. Add 3-aminopropyltriethoxysilane to the above-mentioned sulfur-doped magnesium-aluminum-nickel hydrotalcite nanosheet dispersion, stir evenly, and then add an equal amount of solution each time and spin-coat it on polyimide at a speed of 1000 rpm for 12 seconds. The formed wet film is preliminarily dried in an 80°C drying oven for aminoalkylsilane, and then spin-coated and dried again, for a total of 14 coatings. It is then placed in an air atmosphere at 80, 110, and 150°C for heat treatment for 1h, 1h, and 3h, respectively. Finally, a sulfur-doped ternary hydrotalcite coating with a nearly hexagonal layered structure can be obtained.
[0038] The advantages of the method of the present invention are: a ternary hydrotalcite solution is prepared by a hydrothermal growth method to form regular nanosheets. The coating is prepared by a spin coating method, which is simple in process and convenient in operation; the prepared sulfur-doped ternary hydrotalcite nanosheet composite coating is uniform in film formation, exhibits excellent anti-proton oxygen, antistatic, and UV resistance properties, and improves the flexibility of the coating; the use of an amino-hydrocarbon silane coupling agent not only strengthens the cross-linking degree between the hydrotalcite sheets, but also enables the coating to be firmly bonded to the substrate, significantly improving the adhesion of the coating.
[0039] Performance Test: The anti-protooxygen corrosion performance of the samples was characterized by ground-based atomic oxygen simulation test equipment, and the mass loss was measured using a precision balance. The thermal stress cracking resistance of the samples was characterized by space-time thermal cycle simulation test equipment. The bonding strength between the coating and the substrate was characterized by the hundred-grid knife scratch test, which involved observing the crosshatch with 3M610 tape. ATR-FTIR was used to observe the bonding state of the samples. A scanning electron microscope was used to observe the surface and cross-sectional morphology of the samples.
[0040] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0041] Example 1 (1) Preparation of magnesium aluminum nickel ternary hydroxide. Dissolve 0.65056g magnesium chloride hexahydrate, 0.38628g aluminum chloride hexahydrate, and 0.38030g nickel chloride hexahydrate in deionized water, add ammonia water and stir to adjust the pH to 9-10, stir evenly and let stand. Wash the resulting suspension with deionized water to precipitate the pH to 8-9. After washing, prepare a dispersion with a mass concentration of 20mg / mL. Then place the dispersion in an oven at 150°C and hydroheat for 24h. Finally, a layered hydrotalcite nanosheet dispersion is obtained; (2) The obtained ternary hydrotalcite nanosheets were centrifuged and vacuum dried to obtain ternary oxide powder. The obtained ternary oxide powder was calcined in air at 450°C for 5 hours, and the calcined powder was ground and blended with thiourea at a Ni:S molar ratio of 1:2; the blended powder was reacted at 250°C for 2 hours to obtain a nickel sulfide / ternary oxide mixture; (3) The nickel sulfide / ternary oxide powder was dissolved in deionized water at 80°C and stirred for 6 hours to prepare a 20 mg / mL sulfur-doped ternary hydrotalcite nanosheet aqueous dispersion. 3-aminopropyltriethoxysilane (60 μL) was added to 30 mL of the solution and stirred evenly (wherein the ratio of hydrotalcite nanosheets to silane coupling agent was 10 mg: 1 μL). Each time, an equal amount of solution was added and spin-coated on the modified polyimide substrate at a speed of 1000 rpm for 12 seconds. The formed wet film was preliminarily dried in an oven at 80°C, and then spin-coated and dried again, for a total of 14 times. It was then placed in an air atmosphere at 80, 110, and 150°C for heat treatment for 1 hour, 1 hour, and 3 hours, respectively. Finally, the above-mentioned layered sulfur-doped ternary hydrotalcite nanosheets were obtained.
[0042] Example 2 The preparation process of the sulfur-doped ternary hydrotalcite-like structured anti-proton oxygen coating in Example 2 is similar to that in Example 1, with the only difference being that in step (1), the amount of nickel chloride hexahydrate added is 0 g, and the amount of cobalt chloride hexahydrate added is 0.38069 g.
[0043] Example 3 The preparation process of the sulfur-doped ternary hydrotalcite-like structured anti-proton oxygen coating in Example 3 is similar to that in Example 1, except that in step (1), the amount of nickel chloride hexahydrate added is 0 g, and the amount of cupric chloride dihydrate added is 0.27277 g.
[0044] Example 4 The preparation process of the sulfur-doped ternary hydrotalcite-like structured anti-oxygen / antistatic / ultraviolet-resistant coating in Example 4 is similar to that in Example 1, except that the calcined powder and thiourea are mixed at a Ni:S molar ratio of 2:1.
[0045] Example 5 The preparation process of the sulfur-doped ternary hydrotalcite-like structured anti-oxygen coating in Example 5 is similar to that in Example 1, except that the calcined powder and thiourea are mixed at a Ni:S molar ratio of 1:8.
[0046] Comparative Example 1 The preparation process of the sulfur-doped ternary hydrotalcite-like structured anti-proton oxygen coating in Comparative Example 1 refers to that in Example 1, except that in step (1), the amount of nickel chloride hexahydrate added is 0 g.
[0047] Comparative Example 2 The preparation process of the sulfur-doped ternary hydrotalcite-like structured anti-proton oxygen coating in Comparative Example 1 refers to that in Example 1, with the only difference being that in step (2), the amount of thiourea added is 0 g.
[0048] Comparative Example 3 The preparation process of the sulfur-doped ternary hydrotalcite-like structured antiproton oxygen coating in this comparative example 3 refers to that in Example 1, with the only difference being that in step (2), 3-aminopropyltriethoxysilane (0 μL) is added to the sulfur-doped ternary hydrotalcite-like nanosheet dispersion (30 mL), and an equal amount of the solution is added dropwise each time and spin-coated on the modified polyimide film substrate at a speed of 1000 rpm for 12 s.
[0049] Comparative Example 4 The preparation process of the sulfur-doped ternary hydrotalcite-like structured antiproton oxygen coating in Comparative Example 4 refers to Example 1, with the only difference being that in step (2), 3-aminopropyltriethoxysilane (120 μL) was added to the sulfur-doped ternary hydrotalcite-like nanosheet dispersion (30 mL), and an equal amount of the solution was added dropwise each time and spin-coated on the modified polyimide film substrate at a speed of 1000 rpm for 12 s.
[0050] Table 1 shows the composition of the anti-oxygen / antistatic / ultraviolet resistant composite protective coating of the present invention:
[0051] Table 2 shows the performance parameters of the anti-oxygen / antistatic / ultraviolet resistant composite protective coating of the present invention: In Example 1 of the present invention, the mass loss is negative because under the action of atomic oxygen and ultraviolet radiation, the material has no mass loss, but an increase in mass due to the adsorption of atomic oxygen, which shows that the material has more excellent resistance to atomic oxygen and ultraviolet resistance.
[0052] The raw materials listed in the present invention, as well as the upper and lower limits and interval values of the raw materials of the present invention, and the upper and lower limits and interval values of the process parameters can all realize the present invention, and the embodiments are not listed one by one here.
[0053] Finally, it is necessary to explain here that the above embodiments are only used to further illustrate the technical solution of the present invention in detail and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above content of the present invention all fall within the scope of protection of the present invention.
Claims
1. An anti-oxygen / antistatic / ultraviolet resistant composite protective coating, characterized in that: include: A polymer matrix and a sulfur-doped ternary hydrotalcite protective layer formed on the surface of the polymer matrix; the sulfur-doped hydrotalcite protective layer comprises a silane coupling agent and a sulfur-doped ternary hydrotalcite nanosheet composite material.
2. The anti-proton oxygen / antistatic / ultraviolet resistant composite protective coating according to claim 1, characterized in that: The molar chemical composition of the sulfur-doped ternary hydrotalcite nanosheet composite material is [M 2+ (1-x) / 3 M 2+ (2-2x) / 3 M 3+ x S y 2- (OH) 2-2y ] x+ A n- x / n mH2O; Among them, M 2+ is a divalent metal cation, preferably Mg 2+ 、Ni 2+ 、Co 2+ 、Zn 2+ , Cu 2+ At least two of the following; M 3+ is a trivalent metal cation, preferably Al 3+ Cr 3+ , Fe 3+ Sc 3+ At least one of; A n- For CO3 2- 、NO3 - , Cl - OH - 、SO4 2- PO4 3- 、C6H4(COO)2 2- At least one of; x=0.17~0.33。 3. The anti-proton oxygen / antistatic / ultraviolet resistant composite protective coating according to claim 2, characterized in that: The sulfur-doped ternary hydrotalcite-like composite material has M 2+ 、M 2+ 、M 3+ The molar ratio is (0.67-1.65):(1.36-3.24):1, preferably 1:2:
1.
4. The anti-proton oxygen / antistatic / ultraviolet resistant composite protective coating according to claim 1, characterized in that: The thickness of the hydrotalcite-like nanosheets in the sulfur-doped ternary hydrotalcite-like nanosheet composite material is 0.5-20 nm, and the diameter of the circumscribed circle is 50-500 nm; wherein the sulfur-doped ternary hydrotalcite-like nanosheet composite material is self-assembled and stacked to form a three-dimensional conductive network.
5. The anti-proton oxygen / antistatic / ultraviolet resistant composite protective coating according to claim 1, characterized in that: The silane coupling agent is selected from at least one of aminohydrocarbon silane, 3-mercaptopropyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane and 3-methacryloxypropyltrimethoxysilane; the aminohydrocarbon silane is selected from at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and N-aminoethyl-3-aminopropyltriethoxysilane, preferably 3-aminopropyltriethoxysilane; The silane coupling agent simultaneously undergoes bonding reactions with the polymer matrix and the sulfide / hydrotalcite-like nanolayer.
6. The anti-proton oxygen / antistatic / ultraviolet resistant composite protective coating according to claim 1, characterized in that: The ratio of the sulfur-doped ternary hydrotalcite nanosheet composite material to the silane coupling agent is 10 mg: (0.1-10) μL.
7. The anti-proton oxygen / antistatic / ultraviolet resistant composite protective coating according to claim 1, characterized in that: The thickness of the sulfide / hydrotalcite-like protective layer is 50 nm to 10 μm.
8. The anti-proton oxygen / antistatic / ultraviolet resistant composite protective coating according to any one of claims 1 to 7, characterized in that: The polymer matrix is a polymer matrix containing hydroxyl groups and carboxyl groups or a polymer matrix whose surface is modified to generate hydroxyl groups and carboxyl groups, preferably a polyimide matrix, a fluoroplastic matrix or a polyester matrix.
9. A method for preparing the anti-proton oxygen / antistatic composite protective coating according to any one of claims 1 to 8, characterized in that: include: A silane coupling agent is added to an aqueous dispersion containing a sulfur-doped ternary hydrotalcite nanosheet composite material and mixed, then coated on a polymer substrate surface, and finally heat treated at 80-200° C. for 3-12 hours to obtain the anti-proton oxygen / antistatic composite protective coating.
10. The preparation method according to claim 9, characterized in that: The polymer matrix is surface modified to form groups containing hydroxyl groups and carboxyl groups; Preferably, the surface of the polymer matrix is subjected to alkali-acid modification; the alkali-acid modification includes alkali treatment and acid treatment. More preferably, the polymer matrix is treated in a NaOH solution with a concentration of 0.1 to 6 mol / L and an acetic acid solution with a concentration of 0.1 to 6 mol / L for 0.2 to 6 h, and then washed and dried to obtain a polymer matrix having surface active groups (hydroxyl groups, carboxyl groups); The total concentration of the sulfur-doped ternary hydrotalcite nanosheet composite material in the aqueous dispersion containing the sulfur-doped ternary hydrotalcite nanosheet composite material is 1 to 50 mg / mL, preferably 20 mg / mL; The mixing method is grinding.
11. The preparation method according to claim 9, characterized in that: The coating is applied at least once; The coating includes spin coating, drop coating, spray coating or blade coating; Preferably, the spin coating speed is 300 to 2000 rpm, and the spin coating time is 6 to 18 seconds; Preferably, after each coating, preliminary drying is performed, the preliminary drying temperature is 40 to 100° C., and the preliminary drying time is 5 to 50 seconds.
12. The preparation method according to claim 9, characterized in that: The method for preparing the aqueous dispersion containing the sulfur-doped ternary hydrotalcite nanosheet composite material comprises: (1) calcining a ternary hydrotalcite powder at 250 to 550° C. for 2 to 6 hours to obtain a ternary oxide powder; (2) uniformly blending the obtained ternary oxide powder and a sulfur source, and sulfurizing the mixture at 150 to 400° C. for 1 to 5 hours in an inert atmosphere to obtain a sulfide / ternary oxide mixture; (3) dissolving the sulfide / ternary oxide mixture in deionized water at 40 to 100° C. and stirring for 2 to 10 hours to obtain the sulfur-doped ternary hydrotalcite nanosheet composite material; Preferably, the sulfur source is at least one of thiourea, elemental sulfur, thioacetamide, mercaptan, and sodium sulfide.
13. The preparation method according to claim 12, characterized in that: The method for preparing the ternary hydrotalcite nanosheet powder comprises: (1) M 2+ Salt, M 3+ Salt is added as a hydrotalcite precursor to deionized water, and then an alkali solution is added and stirred to adjust the pH to 9-10, and the mixture is stirred evenly and then allowed to stand to obtain a suspension; (2) washing the obtained suspension to obtain a precipitate dispersion; (4) hydrothermally treating the obtained precipitate dispersion at 80 to 200° C. for 6 to 48 hours to obtain an aqueous dispersion containing ternary hydrotalcite nanosheets; (5) centrifugally drying the obtained uniform dispersion to obtain ternary hydrotalcite nanosheet powder; Preferably, the alkaline solution is aqueous ammonia; Preferably, the concentration of the precipitate dispersion is 1 to 50 mg / mL.
14. Use of the anti-proton oxygen / antistatic composite protective coating according to any one of claims 1 to 8 in the field of space environment.